SECURE USER AUTHENTICATION IN THE CLOUD: LEVERAGING FACE RECOGNITION TECHNOLOGY - Yellamma Pachipala; Muzamil Raheman Shaik; Jaya Ram Samavedam; Anvitha Peddineni; V V R Maheswara Rao (Proceedings on Engineering Sciences)
The demand for safe and convenient authentication techniques is critical in a time when cloud computing is becoming more and more prevalent. The usefulness of face recognition technology—more especially, the ArcFace algorithm—as a dependable method for safe user authentication in cloud services is investigated in this work. It analyses the technology's efficacy in light of more established authentication techniques, weighs its advantages and disadvantages, and discusses privacy concerns. This research emphasizes the potential of face recognition technology to meet the changing needs of cloud computing, stressing the critical balance between security and user-friendliness. It accomplishes this by emphasizing the significance of secure cloud-based authentication, taking into account real-world applications, and resolving security and privacy concerns.